Waste management by restaurant operators in Petaling Jaya / Nasr Eldin Abdallah Elshrif Ebrahiem - Elshrif Ebrahiem, Nasr Eldin (2015)

(untitled)
There are number of factors contribute to municipal waste generation growth rate globally and locally factors are represented by increasing population levels, development, rapid urbanization and the rise in community living standards. Malaysia municipal waste is growing rapidly due to influence by these factors. This makes improving waste management practice highly demanded in every sector producing this waste. Restaurants have credible share in municipal waste as one of major waste source globally and in Malaysia as well, therefore this increase the necessity of study waste management practice among restaurants. This study aims to investigate waste management practice among restaurants in Petaling Jaya city with reference to the compliance, awareness on waste management, and incorporating these findings on waste management practice. The study was done using two approaches; the first approach way a survey to study the compliance of the restaurants to the Local Government Act (LGA) 1976 and that was done by researcher walkthrough investigation. The second approach was done by questionnaire through personal interview by the researcher. SS2 district has been suggested by Petaling Jaya city council for being the most complied area. Perception and waste management practice were assessed by e-checklists prepared according to Green Restaurant Checklist prepared by Burbank Green Alliance, January 2009 and Supplemental Checklist for Restaurants and Food Service prepared by Green Business Program, February 23 2010. Perception and waste management practice were done based on interview by modifying the checklists into questionnaire. The data of this study has been analyzed manually by analyzing the closed-ended questions and answers and then find out the total result from different parts in the study. Compliance study is to assess commitment of restaurants operators to the Local Government Act 1976. , which find 93% compliance among the surveyed restaurants. Perception study on waste management is to find out level of understanding by restaurants operators on waste management iv aspects. The total result of perception study on waste management was 21%. Waste management practice is converting perception of restaurants operators on good waste management performance. The total result of waste management practice performance was 66%. Therefore, the result of waste management practice comes as effort of empowering the Act which gives restaurant operators high compliance.